Answer:
x = 4
Step-by-step explanation:
√x + 1 = 3
√x = 3 - 1
√x = 2
(√x)² = (2)²
x = 4
Answer:
✨how would i help with this ?✨
Step-by-step explanation:
✨:) here to help✨
✨GOD LOVES YOU✨
<h3>Answer:</h3>
13 years old
<h3>Explanation:</h3>
Let g and m represent grandfather's age now and my age now. The relation 5 years ago was ...
... g -5 = 5(m -5)
The relation in 3 years will be ...
... g +3 = 3(m +3)
Subtracting the first equation from the second, we get ...
... 8 = -2m +34
... 2m = 26 . . . . . add 2m-8
... m = 13
My age now is 13.
Well if you write the statement as an equation then that will get you
3*x^2 = 12x
Now we just solve. You can divide both sides by 3x and that gives you x = 4